Gender stereotyping by location, female director appointments and financial performance - Li, Compton Ying (2020)
We investigate whether female board representation and firms’ financial performance are related and whether the relationship differs for firms located in more prejudicial environments. As a proxy for prejudicial environment, we use two geographical indicators: (1) whether a firm is headquartered in a conservative “red” state (which tends to vote for Republican candidates) or in a liberal “blue” state (which tends to vote for Democratic candidates) and (2) whether the firm is located in regions where residents possess more stereotypical attitudes about gender equality. We find that both financial performance and female board representation are lower for firms headquartered in red states when compared to those in blue states, and we find similar results for firms located in regions where residents hold more gender-stereotypical views. However, financial performance improves when female directors are present regardless of the firm’s location. Evidence also shows that the incremental improvement in performance measured by Tobin’s q is greater in red-state than in blue-state companies and in regions where residents hold more gender-stereotypical views. The overall results imply that gender stereotyping holds back financial performance and that female directors help improve financial performance.